Does Monetary Policy Stabilize the Exchange Rate Following a Currency Crisis? - Goldfajn, Ilan (IMF Working Papers; Working Paper, 1999)
This paper provides evidence on the relationship between monetary policy and the exchange rate in the aftermath of currency crises. It analyzes a large data set of currency crises in 80 countries for the period 1980-98. The main question addressed is: Can monetary policy increase the probability of reversing a postcrisis undervaluation through nominal appreciation rather than higher inflation? We find that tight monetary policy facilitates the reversal of currency undervaluation through nominal appreciation. When the economy also faces a banking crisis, the results are not robust: depending on the specification, tight monetary policies may not have the same effect.